Stimuli-Responsive Polymer Nanoprobes Intended for Fluorescence-Guided Surgery of Malignant Head-and-Neck Tumors and Metastases - Pola, Robert; Grosmanová, Eliška; Pechar, Michal; Horák, Dominik; Krunclová, Tereza; Pankrác, Jan; Henry, Maxime; Kaňa, Martin; Bouček, Jan; Šefc, Luděk; Coll, Jean-Luc; Etrych, Tomáš (Advanced healthcare materials, 2023)
Nano-sized carriers are widely studied as suitable candidates for the advanced delivery of various bioactive molecules such as drugs and diagnostics. Herein, the development of long-circulating stimuli-responsive polymer nanoprobes tailored for the fluorescently-guided surgery of solid tumors is reported. Nanoprobes are designed as long-circulating nanosystems preferably accumulated in solid tumors due to the Enhanced permeability and retention effect, so they act as a tumor microenvironment-sensitive activatable diagnostic. This study designs polymer probes differing in the structure of the spacer between the polymer carrier and Cy7 by employing pH-sensitive spacers, oligopeptide spacers susceptible to cathepsin B-catalyzed enzymatic hydrolysis, and non-degradable control spacer. Increased accumulation of the nanoprobes in the tumor tissue coupled with stimuli-sensitive release behavior and subsequent activation of the fluorescent signal upon dye release facilitated favorable tumor-to-background ratio, a key feature for fluorescence-guided surgery. The probes show excellent diagnostic potential for the surgical removal of intraperitoneal metastasis and orthotopic head and neck tumors with very high efficacy and accuracy. In addition, the combination of macroscopic resection followed by fluorescence-guided surgery using developed probes enable the identification and resection of most of the CAL33 intraperitoneal metastases with total tumor burden reduced to 97.2%.
Keywords: fluorescence; Fluorescent Dyes; Cell Line, Tumor; stimuli-sensitiveness; nádorové mikroprostředí; nádory hlavy a krku; Polymers; lidé; guided surgery; fluorescenční barviva; polymer probes; Head and Neck Neoplasms; HPMA copolymers; polymery; Stimuli Responsive Polymers; chytré polymery; Tumor Microenvironment; Fluorescence; nádorové buněčné linie; Humans